A Tempest and The Tempest: Aimé Césaire and Shakespeare - Kaul, Mythili (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
Through an analysis of the play, the article seeks to demonstrate that Aimé Césaire’s A Tempest is a “reinscription” of Shakespeare’s The Tempest as “a drama of rebellion.” It is told from the point of view of “the loser”, Caliban, the “colonized”, who confronts and defies Prospero who has usurped the island and deprived him of his patrimony. He demands his freedom and refuses to accept the “hegemonic europocentric vision of the universe.” Césaire “demythifie[s]” Prospero who is not the benign Magus figure of traditional criticism but the “prototypical colonizer,” a despot, “the complete totalitarian.” The paper argues that, although he never mentions him, Césaire is influenced by George Lamming’s radical reading of Shakespeare’s play through “colonial” and “national” lenses, a reading that anticipates that of Stephen Greenblatt and the New Historicists and pre-empts the question of “linguistic colonialism” which is so crucial to them. While the colonial paradigm has featured in recent discussions of the plays and Césaire and Lamming have been grouped together, the article analyzes and applies Lamming’s reading to both Shakespeare and Césaire and provides a fresh reading of both. The article also goes beyond the argument of Greenblatt and the New Historicists. A Tempest ends equivocally, on a questioning note, and Lamming observes that the Epilogue in The Tempest leaves the latter work, too, somewhat open-ended, a point that is taken up and discussed. The article in conclusion gives a significant, new interpretation, of the titles of the two plays which ties up with and highlights the theme of colonialism which is the focus of both plays.